Twenty "must-read" research articles for primary care providers in Nunavik: scoping study and development of an information tool. Issue 1 (1st January 2019) - Paquin, Vincent; Sandy, Glenda; Perrault-Sullivan, Gentiane; Fortin, Gabriel; Cauchon, Michel; Fletcher, Christopher; Ouellet, Jean; Lemire, Mélanie
ABSTRACT: While health needs in Nunavik are distinct, there is a scarcity of knowledge transfer intended for local primary care providers. We aimed to build an information tool in the form of a newsletter and a website to share with them a selection of relevant research articles. To identify such articles, a scoping study of Inuit health research published between 2012 and 2017 was conducted. Selection criteria were adapted from the framework of information mastery. After a database search yielding 2896 results, publications were screened for eligibility. Next, the 226 eligible articles were evaluated and scored for their relevance, their methods (including community participation), their local applicability and their clinical utility. The 20 highest-scored articles were selected for dissemination in a newsletter. They were summarised and presented in 6 thematic emails: Child Development, Infectious Diseases, Traditional and Modern Medicine, Metabolism, Nutrition and Contaminants, and Inuit Perspectives. The newsletter was sent to over 190 health workers and regional stakeholders in Nunavik and was also published online. We hope that this project will foster knowledge sharing and inter-sectorial collaboration between research, public health and clinical care. Trends in Inuit health research are discussed.